The Letter to Philemon - McKnight, Scot 1953- (Chicago Wm. B. Eerdmans Publishing Co., 2017)
Intro -- Title Page -- Copyright -- Contents -- Dedication -- General Editor's Preface -- Author's Preface -- Abbreviations -- Bibliography -- INTRODUCTION -- I. Slavery in the Roman Empire -- A. Status and Slaves -- B. On Defining "Slavery" -- C. Family Life for the Slave -- D. The Pragmatics of Masters and Slaves -- E. Slavery, No Matter the Explanation -- F. The Options for the Slave -- G. The Runaway -- H. Manumission -- I. Christians and Slaves -- II. Philemon in the Crucible of New World Slavery and Slavery Today -- III. Authorship and Date -- IV. The Social Realities of Philemon: Runaway or Slave in Search of a Mediator? -- V. The Events at Work in the Letter to Philemon -- VI. Structure, Rhetoric and Clarity of Philemon -- TEXT AND COMMENTARY -- I. Introduction (vv. 1-3) -- A. Authors (v. 1a) -- B. Addressees (vv. 1b-2) -- C. Salutation (v. 3) -- II. Thanksgiving (vv. 4-7) -- III. Paul's Appeal for Onesimus (vv. 8-22) -- A. First Appeal in the Sketch of the Scene (vv. 8-11) -- B. Second Appeal in the Presentation of Onesimus (vv. 12-16) -- C. Third Appeal in their Partnership (vv. 17-21) -- D. Final Appeal in a Presence (v. 22) -- IV. Conclusion (vv. 23-25) -- Index of Subjects -- Index of Authors -- Index of Scripture and Other Ancient Texts.
Description based on publisher supplied metadata and other sources
Keywords: Bible.--Philemon--Commentaries; Electronic books; Kommentar